2014
DOI: 10.1111/nicc.12077
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' self‐confidence and attitudes in using the Glasgow Coma Scale: a primary study

Abstract: Mentoring and educational interventions are suggested in order to reduce safety risks resulting from lower proficiency in using the GCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…To distinguish correlation between head AIS scores (1-6) and GCS (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), an analysis was performed. The correlation coefficient Pearson's r was significant at p < .001, with a weak, inverse relationship of -0.3980.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To distinguish correlation between head AIS scores (1-6) and GCS (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), an analysis was performed. The correlation coefficient Pearson's r was significant at p < .001, with a weak, inverse relationship of -0.3980.…”
Section: Resultsmentioning
confidence: 99%
“…[5] The missing GCS score in the clinical setting is often related to the lack of training and nurses' lack of confidence in GCS proficiency. [6] It is imperative to have consistent methods of TBI severity stratification.…”
Section: Introductionmentioning
confidence: 99%
“…The overall objective of the study was checked by comparing the means and SD of this study with previous studies (Chan & Matter 2013, Mattar et al 2014) done on the same topic. To test research questions one and two, a correlation coefficient will be computed.…”
Section: Discussionmentioning
confidence: 99%
“…GCS is considered easy to use; however, this character opens it to misinterpretation and misapplication. (Mattar et al, 2014;McLernon, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although with time and experience nurses' knowledge improves (Mattar et al, ; Santos, Vancini‐Campanharo, Lopes, Okuno, & Batista, ; Reith et al, ), knowledge and skills obtained from education and experience in the GCS are reported to enhance accuracy and ability to use the GCS tool (Ellis & Cavanagh, ; Hansen, Norris, & Sceriha, ; Heron et al, ; Mattar, Liaw, & Chan, ). Additionally, with time, nurses attained more self‐confidence in using the GCS (Chan, Mattar, & Taylor, ; Mattar, Liaw, & Chan, ), and a more positive attitude was associated with increased self‐confidence (Shoqirat, ). For nurses working in the field of neurosciences, evidence suggests that their knowledge of the GCS is inadequate (Jaddoua, Mohammed, & Abbas, ) and that nurses lack confidence in its use (Ehwarieme & Anarado, ).…”
Section: Literature Review/backgroundmentioning
confidence: 99%